A Study on Different Brands of Zinc Fertilizers Available in the Markets of Chuadanga Region (Journal of Environmental Science and Natural Resources, 2016)
A study was conducted in Damurhuda upazila under Chuadanga district from January to December, 2014 to collect information on names, numbers and comparative availability of different brands of Zinc fertilizers in order to aid the assessment of nutrient status for quality of the brands. For this purpose, information was collected from 30 randomly selected fertilizer shops (10 BCIC fertilizer dealers and 20 retailers) through questionnaire interview. In the study total 80 brands [41 Zinc sulfate (mono), 22 Zinc sulfate (hepta) and 17 Chelated zinc] of zinc fertilizer marketed by 51 companies were found in the upazila. Grogin, Topaz, Zinc Sulfate, Mukta Plus, Zingsul, Hay Zinc+ of Zinc sulfate (mono) brands, Topaz and Petro zinc of Zinc sulfate (hepta) brands and Brexil, Field Marshal, Topaz of Chelated zinc brands were most available. Grogin of Zinc sulfate (mono) and Topaz of Zinc sulfate (hepta) were the top most available. Five percent of Zinc sulfate (mono) and nine percent of Zinc sulfate (hepta) mentioned no registration number. No maximum retail price (MRP) was mentioned in seven percent of Zinc sulfate (mono). There was a significant difference between highest and lowest MRP of imported Zinc sulfate (mono) and Chelated zinc brands.J. Environ. Sci. & Natural Resources, 8(2): 103-107 2015